Paradigm Of Continuity Of The Educational Process And Education In A Higher Education Institution (Global Scientific Review, 2024)
The authors presented the results of a study of the continuity of the educational process and education in a higher educational institution. Educational processes are an integral part of learning. This is the right trend, since it is important not only for students to acquire professional competencies and knowledge, but also the ability to be specialists with deep cultural properties, including ethical and deontological aspects of the medical profession. The psychological readiness of a good specialist for his professional activity is expressed in his ability to conduct a correct conversation and communicate with patients and their relatives. Thus, educational work in universities, aimed at developing a well-founded high self-esteem of future young specialists, will contribute to the development of broad universal, general professional and professional competencies. The educational work constantly carried out by higher school teachers is aimed at preparing precisely such highly erudite doctors.